Anatomical Reconstruction of the Glenoid with an Autogenous Tricortical Iliac Crest Bone Graft in Patients with Recurrent Anterior Shoulder Dislocation (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the role of anatomical reconstruction of the glenoid with an autogenous tricortical iliac crest bone graft in patients with recurrent anterior shoulder dislocation in terms of improvement in mean ASES, UCLA and Rowe scores. Design: Descriptive case series. Place and Duration of Study: This study was conducted in the Department of Orthopedics, Sir Ganga Ram Hospital, Lahore from October 2014 to September 2015. Patients and Methods: 30 patients presenting in the orthopedic outpatient department of Sir Ganga Ram Hospital, Lahore with recurrent anterior shoulder dislocation and MRI evidence of Bankart lesion along with glenoid bone loss were included in this study. A written informed consent was taken from every patient. Results: The mean age of the patients was 40.10±8.23 years and there were 28 (93.3%) male and 2 (6.7%) female patients in the study group. Pre-operative ASES score ranged from 44 to 78 with a mean of 59.63±10.30, UCLA score ranged from 14 to 29 with a mean of 23.50±4.51 and Rowe score ranged from 15 to 40 with a mean of 26.33±6.69. Post-operative ASES score ranged from 75 to 100 with a mean of 89.07±7.91, UCLA score ranged from 30 to 35 with a mean of 33.13±1.46 and Rowe score ranged from 85 to 100 with a mean of 96.00±4.02. The difference between mean pre and post-operative ASES (59.63±10.30 vs. 89.07±7.91; p=.000), UCLA (23.50±4.51 vs. 33.13±1.46; p=.000) and Rowe (26.33±6.69 vs. 96.00±4.02; p=.000) scores was significant. When stratified the data, there was no significant difference in various age (p≥0.05) and gender (p≥0.05) groups. Conclusion: Anatomical reconstruction of the glenoid with an autogenous tricortical iliac crest bone graft was found to be an effective treatment for patients with recurrent anterior shoulder dislocation irrespective of patient’s age and gender
Keywords: Anatomical Glenoid Reconstruction, Recurrent Anterior Shoulder Dislocation, Autogenous Tricortical Iliac Crest Bone Graft